2009
DOI: 10.1111/j.1475-4754.2008.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Lead Isotope Analyses of Bronze Age Copper‐base Artefacts From Al‐midamman, Yemen: Towards the Identification of an Indigenous Metal Production and Exchange System in the Southern Red Sea Region*

Abstract: The results of the lead isotope analysis (LIA) of 15 copper-base artefacts from the Bronze Age site of al-Midamman, Yemen, are reported. The LIA data suggest the existence of an indigenous Bronze Age metal production and exchange system centred on the southern Red Sea region, distinct from those in neighbouring regions of Arabia and the Levant. These preliminary results are highly significant for the archaeology of the region, suggesting that local prehistoric copper extraction sites have thus far gone unrecor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Computational Fluid Dynamics of wind powered iron furnaces (Tabor et al 2005); the provenancing of ore deposits through isotope ratios of ores, slags and artefacts (Weeks et al 2009); and the microscopic examination of hammerscales, slags, and blooms, to understand production and processing factors (Jouttijärvi 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Computational Fluid Dynamics of wind powered iron furnaces (Tabor et al 2005); the provenancing of ore deposits through isotope ratios of ores, slags and artefacts (Weeks et al 2009); and the microscopic examination of hammerscales, slags, and blooms, to understand production and processing factors (Jouttijärvi 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Cross‐referencing the LI, major element and contextual data for the remaining 11 bangles and bowls is problematic, but they appear to be high‐tin bronzes (ibid.). Maintaining the assumption that tin does not normally bring a significant LI contribution to a copper alloy (e.g., Begemann and Schmitt‐Strecker 2009; Weeks et al . 2009, 586), the LI signature of the 11 high‐tin bronzes can be compared with the nascent SEALIP database (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Weeks et al (2009) suggested three main copper sources within and around Arabia which were exploited since before the Iron Age. Geographically, the most likely copper source for Tayma and Qurayyah would be the Jordan rift valley of northwest Arabia with the famous ancient mining and smelting sites at Feinan and Timna (Rothenberg, 1972;Hauptmann, 2007;Weisgerber, 2006).…”
Section: Lead Isotope Analysismentioning
confidence: 99%
“…The second major potential copper source for these two sites is in current Oman and the northern United Arab Emirates where copper was exploited as early as the second half of the third millennium BC and at least until the pre-Islamic period (Weeks, 2003). The third potential copper source (Weeks et al, 2009) is the so-called Arabian Shield in southwest Arabia and northeast Africa, split by the Red Sea. Lead isotope data for ores and artefacts from this region match best with Bronze Age artefacts from al-Midamman on the Red Sea coast of Yemen (Weeks et al, 2009: 593e4).…”
Section: Lead Isotope Analysismentioning
confidence: 99%